1981
DOI: 10.1083/jcb.89.3.536
|View full text |Cite
|
Sign up to set email alerts
|

Lectin labeling of sprouting neurons. I. Regional distribution of surface glycoconjugates.

Abstract: Well-defined ferritin-conjugated lectins were used to map glycoconjugates on the surface of sprouting neurons from rat superior cervical ganglion (SCG) and spinal cord (SC) . The cultured neurons were exposed to the markers and processed for electron microscopy, and the number of ferritin particles per unit area of plasmalemma was measured in three different regions: perikaryon, neuritic shaft, and growth cone . Three different binding patterns are observed for different lectin : equal receptor density through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(49 citation statements)
references
References 13 publications
2
47
0
Order By: Relevance
“…The Ca2+-dependent membrane fusion in growth cones has been studied by the Phenninger's group, though proteins involved in the fusion have not been identified. They have developed a cell-free membrane expansion assay using intact growth cone particles and found that high potassium depolarization and calcium-ionophore treatment cause significant increases in exposed WGA binding sites within minutes [22,23]. By morphometric analysis, the source of the newly added plasma membranes has been identified as clear vesicles (150 nm in diameter).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ca2+-dependent membrane fusion in growth cones has been studied by the Phenninger's group, though proteins involved in the fusion have not been identified. They have developed a cell-free membrane expansion assay using intact growth cone particles and found that high potassium depolarization and calcium-ionophore treatment cause significant increases in exposed WGA binding sites within minutes [22,23]. By morphometric analysis, the source of the newly added plasma membranes has been identified as clear vesicles (150 nm in diameter).…”
Section: Discussionmentioning
confidence: 99%
“…The source of the membrane for the rapidly growing axolemma and the mode by which the membrane is added to the axolemma have been of primary interest. Pfeninger et al have demonstrated in vitro that some clear vesicles localized in growth cones fuse with the axolemma in a Cat-dependent manner [22,23]. The molecules involved in the Cat-dependent membrane fusion in the growth cones are, however, largely unknown.…”
mentioning
confidence: 99%
“…DRG cultures were fixed by a slow infusion of fixative (4% paraformaldehyde, 0.1 M phosphate buffer, pH 7.4, 120 mM glucose) as described previously (45). Thereafter, any remaining fixative was removed by rinsing the cultures three times with PBS containing 1 mM glycine.…”
Section: Methodsmentioning
confidence: 99%
“…DRG cultures were fixed using slow infusion of 4% (wt/vol) formaldehyde in 0.1 M phosphate buffer, pH 7.4, with 120 mM glucose and 0.4 mM CaCl 2 , as developed for electron microscopy (Pfenninger and Maylie-Pfenninger, 1981). Cultures were rinsed (three times) with phosphate-buffered saline (PBS) containing 1 mM glycine, permeabilized with blocking buffer [PBS, 1% (wt/ vol) bovine serum albumin] plus 1% (vol/vol) Brij 98 detergent for 2 min at room temperature, and placed in blocking buffer for 1 h at room temperature.…”
Section: Fixation and Labeling Of Growth Cones In Culturementioning
confidence: 99%